Філософія самоідентифікації країни в контексті її майбутнього - Кремень, Василь Григорович (НТУ "ХПI", 2010)
Philosophical essence and terms of identity of the country through the structure of appearances and senses of community of historical fate, high spirituality and culture of people are analysed. The ideal two-tier model of self-identification is considered — civil and ethnic, where culture, language and religion of majority come forward as the kernel of cultural sphere of society around which the nation is formed as civil multiethnic education.
Keywords: ідентичність; самоідентифікація; індустріалізація